2018
DOI: 10.1002/1873-3468.13302
|View full text |Cite
|
Sign up to set email alerts
|

Novel functions of peroxiredoxin Q fromDeinococcus radioduransR1 as a peroxidase and a molecular chaperone

Abstract: Deinococcus radiodurans R1 is extremely resistant to ionizing radiation and oxidative stress. In this study, we characterized DR0846, a candidate peroxiredoxin in D. radiodurans . DR0846 is a peroxiredoxin Q containing two conserved cysteine residues. DR0846 exists mainly in monomeric form with an intramolecular disulfide bond between the two cysteine residues. We found that DR0846 functions as a molecular chaperone as well as a peroxidase. A mutational analysis indicates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Consistently, it was reported that a Deinococcus geothermalis mutant lacking the cystine importer system, which is a source of thiols, was more sensitive to an H 2 O 2 treatment [21]. Some studies based on biochemical, pharmacological, or genetic approaches characterised the Trx system in Deinococcus [22][23][24] and indicated that it likely plays an essential role in responses to oxidative stress [25,26]. In a previous review describing Deinococcus antioxidant systems [3], the main TR families were listed, revealing that this bacterial genus possesses a complete Trx system, including a relatively high number of TRs related to Trxs and Prxs.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Consistently, it was reported that a Deinococcus geothermalis mutant lacking the cystine importer system, which is a source of thiols, was more sensitive to an H 2 O 2 treatment [21]. Some studies based on biochemical, pharmacological, or genetic approaches characterised the Trx system in Deinococcus [22][23][24] and indicated that it likely plays an essential role in responses to oxidative stress [25,26]. In a previous review describing Deinococcus antioxidant systems [3], the main TR families were listed, revealing that this bacterial genus possesses a complete Trx system, including a relatively high number of TRs related to Trxs and Prxs.…”
Section: Introductionmentioning
confidence: 78%
“…Cho et al [25] investigated the expression levels of the three bcp genes in D. radiodurans exposed to oxidative stress generated by H 2 O 2 or subjected to gamma irradiation. DR_0846 was strongly induced by both treatments, while the expression of DR_1209 was moderately increased by the peroxide, and that of DR_1208 was substantially triggered by irradiation.…”
Section: Thioredoxin-dependent Peroxidases/peroxiredoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Su et al (30) found that TPx-Q functions as molecular chaperone and peroxidase. Cho et al (58) first reported that Prx Q of Deinococcus radiodurans R1 is a monomeric atypical 2-Cys Prx and has dual activity as peroxidase and a molecular chaperone. However, the molecular chaperones function of BmTPx-Q needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…DR_A0164 is reduced by D. radiodurans Trx reductase (TrxR; DR_1982), which can utilize only NADPH for activity [12]. DR_0846 is a Trx-dependent PrxQ, a homolog of bacterioferritin comigratory protein (BCP), which contains the two closely situated Cys residues (CXXXXC), and it functions as a molecular chaperone as well as a peroxidase [13].…”
Section: Introductionmentioning
confidence: 99%